Nitrogen in Agriculture Updates - Fahad, Shah (IntechOpen, 2018)
Nitrogen is the most yield-restraining nutrient in crop production globally. Efficient nitrogen management is one of the most important factor for improving nitrogen use efficiency, field crops productivity and profitability. Efficient use of nitrogen for crop production is therefore very important for increasing grain yield, maximizing economic return and minimizing nitrous oxide (N2O) emission from the fields and nitrate (NO3) leaching to ground water. Integrated nitrogen management is a good strategy to improve plant growth, increase yield and yield components, grain quality and reduce environmental problems. Integrated nitrogen management (combined use of chemical + organic + bio-fertilizers) in field crop production is more resilient to climate change.